Taâ€™lÄ«m MahÄratai al-IstimÄâ€™ wal al-KalÄm al-Faâ€™â€™Äl min KhilÄl al-Masraá¸¥iyyah al-Ará¸iyyah (Bahá¹¡ TajrÄ«biy fÄ« á¹¬ullÄb al-MustawÄ al-RÄbiâ€™ bi JÄmiâ€™ah Pontianak al-IslÄmiyyah) - Sahrani Sahrani (Jurnal Alsinatuna, 2019)
This Study aims to describe the drama method as one of the methods that is assumed to be able to overcome the problems that have often been faced by students of Pontianak IAIN FTIK, such as shame, fear of speaking wrong and lack of confidence. This research uses mixed methods by using data collection instruments such as observation guidelines, test, interview guidelines, documentation, and non-parametric scales. The results of this study illustrate that the previous methods used by lecturers did not contribute much in realizing student competencies in listening and speaking skills. However, after being given an experiment using the drama method, student competencies increased with an average score of 70,034 listening skills which was previously at 60,884. And at an average rate of 67,069 in the previous speaking skills at 58,690.